India's Decision Making on Cross-Border Natural Gas Pipelines (1989–2012). Issue 5 (2nd September 2016) - Kulkarni, Sanket Sudhir
Abstract: In the last two decades, cross-border gas pipelines have become an integral part of discourse on India's energy security. Successive reports from the government and the private sector have envisaged an important role for cross-border gas pipeline projects in India. After engaging in negotiations for several years, the Indian Government finally joined the Turkmenistan, Afghanistan, Pakistan and India (TAPI) gas pipeline over the Iran–Pakistan–India pipeline (IPI) and the Myanmar–Bangladesh–India pipeline (MBI). Several critics of this project have questioned this decision of the Indian Government to join TAPI due to the huge levels of risks involved and the project's commercial unviability. The article is an attempt to understand the decision-making process of the Indian Government on cross-border gas pipeline projects and its rationale for choosing a seemingly riskier project like the TAPI pipeline and letting go of the other two pipeline projects. The article makes an attempt to conduct a detailed discussion around such factors that contributed to India's decision making on these projects.